2017
DOI: 10.1111/jvim.14720
|View full text |Cite
|
Sign up to set email alerts
|

The Renin‐Angiotensin‐Aldosterone System in Greyhounds and Non‐Greyhound Dogs

Abstract: BackgroundThe renin‐angiotensin‐aldosterone system (RAAS) regulates blood pressure, electrolyte homeostasis, and renal function. Blood pressure, serum sodium concentrations, and urinary albumin excretion are higher in Greyhounds than other purebred and mixed‐breed dogs.HypothesisAlterations in the RAAS in Greyhounds are associated with hemodynamic and clinicopathologic differences observed in the breed.AnimalsClinically healthy Greyhound and non‐Greyhound dogs consecutively enrolled as blood donors (n = 20/gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…20 However, the few articles that describe exercise-associated hyperkalemia also report proportional increases in sodium and chloride concentrations, suggesting this change is likely the result of intravascular fluid translocation or dehydration. [20][21][22][23][24][25] A recent study 26 by one of the authors found that Greyhounds have significantly lower basal aldosterone concentrations than non-Greyhound dogs, despite having similar plasma renin-and angiotensin-converting enzyme activities. It is possible that this contributes to the development of hyperkalemia or the inability of Greyhounds to rapidly or effectively respond to increases in serum potassium concentrations when they occur.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, the few articles that describe exercise-associated hyperkalemia also report proportional increases in sodium and chloride concentrations, suggesting this change is likely the result of intravascular fluid translocation or dehydration. [20][21][22][23][24][25] A recent study 26 by one of the authors found that Greyhounds have significantly lower basal aldosterone concentrations than non-Greyhound dogs, despite having similar plasma renin-and angiotensin-converting enzyme activities. It is possible that this contributes to the development of hyperkalemia or the inability of Greyhounds to rapidly or effectively respond to increases in serum potassium concentrations when they occur.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a Greyhound with a mild increase in creatinine without elevated SDMA concentration. This result can be attributed to the idiosyncrasy of this breed, which presents higher creatinine concentrations [ 34 ] and probably SDMA levels when compared with dogs from other breeds [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other breeds, Greyhounds possess a number of unique hematologic, biochemical, and drug metabolism characteristics and some of these factors could indicate differences in cellular production and metabolism. Indeed, increased SDMA production due to an increased cell turnover rate has been a proposed mechanism for higher SDMA concentrations in juvenile dogs, and could be a potential mechanism in Greyhounds.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study comparing SDMA concentrations between 3 different breeds (Pointers, Cairn Terriers, and Cavalier King Charles Spaniels) found no significant differences . In contrast, SDMA concentrations were significantly higher in Greyhounds (n = 20) compared with other breeds (n = 20), and 68% of Greyhounds had an SDMA concentration greater than the upper limit of the previously established canine RI . Larger studies are required to confirm this latter finding, particularly since Greyhound pet ownership has become increasingly popular, and with this comes greater owner expectations for veterinarians to have breed‐specific knowledge .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation